Characterisation of biomass pyrolysis by stepwise product collection and analysis: Mallee wood - Drzezdzon, Brendan; Larcher, Alf (Elsevier, 2013)
Thermogravimetric analysis (TGA) and pyrolysis–mass spectrometry (PY–MS) have been completed on mallee woody biomass with the generated bio-oil and gases being collected and analysed. Equivalent TGA and PY–MS experiments showed that the TGA differential weight curve was similar to the combined PY–MS CO2 and CO evolution curve. To determine how the product distribution through the pyrolysis process changed with temperature, a series of stepwise temperature experiments was performed using novel isolation and characterisation procedures, where the final PY–MS temperature was chosen to correspond to a specific portion of the total TGA curve. Three stepwise experiments were completed in the same fashion as the full range experiment, but where the final temperatures were 234, 330 and 587 °C respectively. Analysis of the products from the low temperature Step 1 experiment showed an acetic acid-rich bio-oil and a CO2–rich gas had formed, indicative of hemicellulose decomposition. Phenols were also found to be present in this oil indicating that lignin decomposition also had occurred. The Step 2 experiment was characterised by major bio-oil generation with a full range of typical components present, indicating the decomposition of hemicellulose, cellulose and lignin had occurred. The higher temperature Step 3 experiment was mainly characterised by volatiles generation which appeared to be derived from thermal decomposition reactions.